Ontology extraction and evaluation for the Blue Amazon: an experiment with large language models - Soares, Vivian Magri Alcaldi (2025)
The Brazilian maritime territory, also referred to as Blue Amazon, has invaluable significance for its resources, biodiversity, impact on climate regulation etc. Yet, information about it is disperse. Searching for efficient methods with satisfying results for the task of organizing knowledge about it on the form of an ontology, an approach involving Large Language Models (LLMs) in the role of experts for building conceptual hierarchies has shown promising results. This work presents the experimentation with the construction of ontologies using Blue Amazon related concepts aided by GPT, followed by human evaluation and the assessment of the results. This study seeks to shed light on the potential of these models on the aid of ontology crafting.